An Unusual Coexistence of Progressive Pseudorheumatoid Dysplasia and Relapsing Polychondritis - Gamze KILIÇ; Erkan KILIÇ; Özgür AKGÜL; Nimet ATAKUL; Salih ÖZGÖÇMEN (Archives of Rheumatology, 2016)
Progressive pseudorheumatoid dysplasia is a rare hereditary skeletal disease characterized by bone and cartilage dysplasia, progressive arthropathy without sign of systemic or synovial inflammation. Relapsing polychondritis (RP) is a rare autoimmune disease associated with inflammation in cartilaginous and other proteoglycan rich structures. An associated autoimmune and/or hematologic disorder is seen in over 30% of patients with RP. To our knowledge, coexistence of progressive pseudorheumatoid dysplasia and RP has not been previously reported. In this article, we describe an unusual case of coexisting progressive pseudorheumatoid dysplasia with RP. Physicians should be aware of this possible association.